Assédio moral nas relações de trabalhoe e suas implicações para o indivíduo e para a sociedade - Medeiros, Izabela Filgueira de (Universidade Federal Rural do Semi-Árido, 2018)
The present study addressed the main aspects of the moral harassment institute in the labor relations, with regard to the concept, causes, effects and legal aspects. The discussion on this subject is recent and has been gaining space in the legal scene due to the evidence of the fact and a concern to combat violence against the worker in the work environment. Initially, the inherent concepts and their scope at the municipal, state and national levels were initially discussed. The different methods of bullying, the methods, the characteristics of the aggressor and the victim, as well as the consequences of these aggressions for the for the employer, the State and the Society. To exemplify a harassment environment, a case study was conducted at the Water and Sewer Company of Rio Grande do Norte - CAERN, interviewing 50 (fifty) employees of the company. In order to complement and analyze the current situation, issues of bullying in the Brazilian legal system, specific legislation, civil liability and the main cases and jurisprudence on this issue were addressed.
Keywords: Assédio moral; Ordenamento jurídico; Ambiente laboral; Moral harassment; Legal order; Labor environment; CIENCIAS SOCIAIS APLICADAS::DIREITO